MODERN RACISM: BINARY OPPOSITION OF BLACK AND WHITE IN THE NOVELS OF JACQUELINE WOODSON - Al-Hafizh, Muhammad; Faruk, Faruk; Juliasih, Juliasih (English Department FBS UNP, 2016)
The meaning of thing in a discourse is potentially determined by soemoene who has the power. In this case, a discourse is purposely designed and conditioned by dominan institution. Through the language in a discourse, some bad characters or images can be attributed to someone such as subversive, fundamentalist, terrorist, and so on. Such phenomena also can be found in the terminology of black and white in the discourse about racism. Black is identical as the opposition of white. Whereas black is bad, white always has connotation with good things, such as purity, God, excellence, etc. Binary opposition of white and black is continously produced in the discourse about racism. Black people (negroid) are assumed inferior toward white (caucasoid). At the same time, language also contribute positive image toward people who have the authority. In that case, language is not only a grammatical system, but it leads to the conflict of interest. This paper is a result of library research toward a discourse about racism in the novels of Jacqueline Woodson. The research was conducted by using poscolonialism and deconstruction approach. This reserach is aimed at revealing: (1) how are the image about black and white are constructed in the novels of Jacqueline Woodson. (2) What are the binary opposition, decentering and fixasion aspects in that novels. The conclusion of this research shows that language is still powerfull in shaping ideas about racism, especially in keeping the issues of black and white as binary opposition.Â Â Key words: discourse, binary opposition, power, racism